Clinical-pathological concordance in deceased at the Cienfuegos Pediatric Hospital, 2000-2015 - Jorge Luis Capote Padrón; Yusimí García Mena; Ariel Efrén Uriarte Méndez; Alnilam Fernández González; Darian Polls Machado; Dunia María Chávez Amaro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: Causes of death concordance and discrepancy between the clinical and the morphological diagnoses are, indirectly, indicators of quality in hospital care, and have played a fundamental role in medical education. Objective: to describe the behavior of the clinical-pathological concordance in a series of pediatric deaths. Methods: an observational, descriptive study was carried out in the Cienfuegos Pediatric Hospital, from January the 1st 2000 to December the 31st, 2015, which included 214 deaths with autopsies. Of the total that was analyzed, 36 deceased from 2013 were classified by the Goldman method. Results: infectious diseases predominated in all age groups, pneumonia and sepsis were the most frequent. Multiple organ dysfunction syndrome was the condition most described as a direct cause of death, linked not only to infectious diseases, as it also manifested as a final event. A low frequency of clinicopathological diagnostic discrepancy was obtained, both for the basic causes of death and for the direct ones, with the 13.6% and the 18.2%, respectively. According to the Goldman classification, the 69.4% of the deceased did not present discrepancies. Conclusion: there was an acceptable clinicopathological correlation during the study period. This variable is useful as a standard for evaluating the medical care quality.